Mind the force majeure clauses in investment contracts - Lu Wang; Wenhua Shan (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2023)
Force majeure clauses in investment contracts are currently in the spotlight, especially due to the COVID-19 pandemic and the Russia-Ukraine war. This Perspective highlights some key issues for parties to consider when declaring force majeure and suggests clarifying contractual language.
Keywords: 330